Complete or High-Quality Draft Genome Sequences of Six Xanthomonas hortorum Strains Sequenced with Short- and Long-Read Technologies - Dia, Nay C. (Microbiol Resour Announc, 2020)
We report the genome sequences of six Xanthomonas hortorum species-level clade members, X. hortorum pathovars taraxaci, pelargonii, cynarae, and gardneri (complete genome sequences) and X. hortorum pathovars carotae and vitians (high-quality draft genome sequences). Both short- and long-read sequencing technologies were used.